Hybrid Qm/Mm Simulations Confirm Zn(Ii) Coordination Sphere That Includes Four Cysteines from the p2 × 4r Head Domain - Garcia Huidobro-Toro, J; Mera-Adasme, R (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
To ascertain the role of Zn(II) as an allosteric modulator on P2X4R, QM/MM molecular dynamic simulations were performed on the WT and two P2X4R mutants suggested by previous electrophysiological data to affect Zn(II) binding. The Gibbs free energy for the reduction of the putative P2X4R Zn(II) binding site by glutathione was estimated at −22 kcal/mol. Simulations of the WT P2X4R head domain revealed a flexible coordination sphere dominated by an octahedral geometry encompassing C126, N127, C132, C149, C159 and a water molecule. The C132A mutation disrupted the metal binding site, leading to a coordination sphere with a majority of water ligands, and a displacement of the metal ion towards the solvent. The C132A/C159A mutant exhibited a tendency towards WT-like stability by incorporating the R148 backbone to the coordination sphere. Thus, the computational findings agree with previous experimental data showing Zn(II) modulation for the WT and C132A/C159A variants, but not for the C132A mutant. The results provide molecular insights into the nature of the Zn(II) modulation in P2X4R, and the effect of the C132A and C132A/C159A mutations, accounting for an elusive modulation mechanism possibly occurring in other extracellular or membrane protein. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.